Is It Safe to Use a Lead Screen During Hip Arthroscopy? - Alexander Rahill, M.B.B.S., B.Physio. (Hons); Leah Biffin; Camdon Fary, B.App.Sci. (Physics); Alasdair G. Sutherland, B.Sc. (Hons); Phong Tran, M.B.B.S. (Hons) (Elsevier, 2021)
Purpose: To assess the radiation attenuation of lead screens in comparison to lead gowns in a simulated hip arthroscopy setting. Methods: In this quantitative laboratory study, a phantom pelvis was used to simulate the scatter produced by patients during hip arthroscopy. Radiation measurements were taken using a handheld radiation detector positioned perpendicular to the phantom pelvis at 1.5 m and 2 m. Measurements were taken without shielding as a control, behind a lead gown (0.4-mm lead equivalent), and behind a lead screen (0.5-mm lead equivalent). Results: With the detector at 1.5 m perpendicular to the hip, equivalent radiation was attenuated by the lead screen (94%) and the lead gown (94%). With the detector at 2 m perpendicular to the hip, the lead screen at 1.7 m attenuated 95% of radiation. Conclusions: In hip arthroscopy, using lead screens is a safe and more comfortable alternative to wearing lead gowns. The lead screen should be at least 1.2 m from the radiation source, with the surgeon standing closely behind the screen, fully covered. Clinical Relevance: Lead screens can be safely used in hip arthroscopy.